A preliminary study on the antimicrobial activity of anacardium occidentale linneus (Kasoy) - De leon, Mylene; Huang, Tsang Chuan; Ortega, Adelwisa (Adviser).
"Health for all by the year 2000" is a vision of the Department of Healtli. However, this vision can not be commonly shared by majority of the Filipinos because their meager income are insufficient to meet the rising cost of the medicines. If these medicinal plants are tested and proven to be effective , more affordable medicines will be made available to the public. This research aimed to determine the antimicrobial activity of the decoction of the leaves of Anacardium Occidentals Linneus otherwise known as Kasoy against streptococcus viridans, streptococcus pyogenes, staphylococcus aureus using the disc diffusion method. These organisms are often associated with oral infection. The experiment was conducted in-vitro using different concentrations against the test microorganism. Based on zones of inhibition, the study tends to show that concentration of 10-¹, 10-², 10-³ and stock preparation of kasoy leaves decoction failed to inhibit microbial growths of streptococcus viridans, streptococcus pyogenes, staphylococcus aureus as compared to ampicillin.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Herbal medicine